Racial Discrimination toward the Black in Stephen Hopkins's Race (2016) Film - Yuliyana, Yuliyana; Muhajir, Fatimah; Alamsyah, Alamsyah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
ABSTRACT Racial discrimination is a social problem that occurred from a long time until today. It can be any negative act such as exclusion, distinction, limitation, or preference for other people on the basis of race, ethnicity, or skin color. Some racial discrimination that happened in our real life is also seen in film as a reflection of real life. There are many films that raise the racial discrimination theme, one of them is Race film by Stephen Hopkins. This research aims to analyze the Racial discrimination specifically types of racial discrimination used Fred L.Pincus theory, and negative impacts of racial discrimination used Settle theory. This research was conducted by using qualitative method. In this research, the researcher took data from script and scene in the film. The results of the research show that there are nine data indicated as types of racial discrimination and five data indicated as the negative impact of racial discrimination against black people in the Race film. In this research, there are three types of racial discrimination that are portrayed in the Race film namely, individual discrimination, institutional discrimination, and structural discrimination. There are three types of negative impacts of racial discrimination toward the blacks namely, health problem, wellbeing problem, and influence emotional reaction. Keywords: film, impacts of racial discrimination, racial discrimination